The Effect of Compensation and Work Environment on Employee Performance with Employee Engagement as a Mediating Variable - Ira Setyawati; Budi Eko Soetjipto; Ludi Wishnu Wardana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of compensation and work environment on employee performance with employee engagement as a mediating variable at PT. Profilindah Kharisma. The compensation variable is measured through the level of pay, benefits, raises, and pay structure; the work environment through job complexity, autonomy, workload, supervisor support, and coworker relationships; employee engagement through emotional involvement, responsibility, concern, and task completion; while employee performance is measured through task completion, work standards, efficiency, result orientation, and creativity. The study used a quantitative approach with the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. Data were obtained from 155 employee respondents through questionnaires and analyzed using SmartPLS 3.0. The results showed that compensation and work environment had a positive and significant effect on employee performance. In addition, employee engagement also has a significant effect on performance and mediates the relationship between compensation and work environment with performance. The implication of this study is the need for management to integrate a fair compensation system, a conducive work environment, and engagement enhancement programs to support sustainable performance. Further research is recommended to add variables of leadership or organizational culture to provide more comprehensive results